Blue carbon oxidation revealed by radiogenic and stable isotopes in a mangrove system. Issue 10 (27th May 2017) - Maher, Damien T.; Santos, Isaac R.; Schulz, Kai G.; Call, Mitchell; Jacobsen, Geraldine E.; Sanders, Christian J.
Abstract: Mangroves are among the most carbon‐rich ecosystems on Earth and can sequester carbon in sediments over long timescales. Here we assess whether century‐old buried carbon may be remineralized and exported by measuring Δ 14 C in the exported dissolved inorganic carbon (DIC) as well as sediment Δ 14 C profiles in a subtropical mangrove. Pore water exchange released isotopically depleted, old DIC to surface waters. Keeling plots revealed that the source of DIC to surface waters had a δ 13 C‐DIC value of −29.4 ±1.9‰ and Δ 14 C‐DIC value of −73±9‰. The respired and exported carbon comes from an average depth of 40 cm, equivalent to 100 years of sediment accumulation. Therefore, century‐old sequestered carbon is still susceptible to remineralization and tidal export to the coastal ocean via pore water exchange or submarine groundwater discharge. We suggest that the timescales over which blue carbon burial is assessed should consider carbon losses via pore water exchange. Key Points: Water column radiocarbon and pore water tracers (radon and radium) were measured in a mangrove system over a tidal cycle Pore water exchange likely resulted in the export of aged inorganic carbon, from the mineralization of buried organic carbon The activity of bioturbating fauna (e.g., crabs) and the formation of macropores by decaying roots appears to enhance oxidation of "blue" carbon